2015
DOI: 10.18805/ijar.7495
|View full text |Cite
|
Sign up to set email alerts
|

Blood clinicopathological differences between type I and II ketosis in dairy cows

Abstract: The purpose was to determine the difference of blood clinicopathological changes between type I and type II ketosis in dairy cow. Fifty-eight cows, from dairy cattle farm in Heilongjiang of China, were included. An ELISA test was used to evaluate the blood indicators. The plasma concentrations of beta-hydroxybutyric acid (BHBA) and insulin sensitivity decreased, and the plasma concentration of glucose (Glc), non-esterified fatty acid (NEFA) and bilirubin content increased in type II ketosis group compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
1
3
1
1
Order By: Relevance
“…The results of our study contrast with those of others report that a period of major fluctuations in serum Ca 2+ occurs between day 7 prepartum (168 hours before calving) and day 7 postpartum (168 hours after calving) and that, as the number of calvings or age increases, cow serum concentrations of Ca 2+ decrease, and incidence of clinical hypocalcemia increases (Samad et al 2002;Meléndez et al 2004) and can cause other associated metabolic disorders (Chapinal et al 2011;Salgado et al 2009;Chuang et al 2016).…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The results of our study contrast with those of others report that a period of major fluctuations in serum Ca 2+ occurs between day 7 prepartum (168 hours before calving) and day 7 postpartum (168 hours after calving) and that, as the number of calvings or age increases, cow serum concentrations of Ca 2+ decrease, and incidence of clinical hypocalcemia increases (Samad et al 2002;Meléndez et al 2004) and can cause other associated metabolic disorders (Chapinal et al 2011;Salgado et al 2009;Chuang et al 2016).…”
Section: Resultscontrasting
confidence: 99%
“…Ketosis has a higher incidence in cows that have had two or more calvings and at the beginning of lactation when milk production is higher (Espino et al 2005;Enjalbert et al 2001;Gilliund et al 2001;Ingvartsen et al 2003;Overton et al 2004). The dairy cow induced ketosis when the concentration of NEFA product more than the demands of body (Chuang et al 2016) Some breeds of dairy cattle, such as Jersey and Guernsey have a high propensity to contract metabolic disorders because they produce colostrum with a higher concentration of Ca 2+ than Holstein cows and because the 1.25 (OH) 2 D 3 receptors are fewer in Jersey cows (Ingvartsen et al 2003;Andresen , 2001). In general, the diseases that occur at a subclinical stage are of great importance in the dairy industry because of economic and health consequences (Suthar et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we found that the serum levels of NEFA, glucose, and insulin were increased in HYK cows at the calving date. In line with our findings, previous studies also reported that increased NEFA levels in HYK dairy cows were accompanied by an increased BHB concentration ( 19 , 44 ). In a poor adaptation state, abundant NEFA are released from the adipose tissue, and further metabolized to TG or BHB in the liver ( 13 ).…”
Section: Discussionsupporting
confidence: 93%
“…A positive correlation was found between BHB values and hepatocyte functional status parameters (bilirubin, AST, GGT) and a negative correlation with TGC (Djoković et al, 2019a). Chuang et al (2016) found differences in the values of individual laboratory parameters in cows with ketosis type 1 and type 2 measured from the moment of calving to the fourth week of lactation and showed a significant deviation of the AST value. Based on the results obtained by González et al (2011), the activity of AST ˃100 IU/L may indicate some degree of liver damage most likely as a consequence of fatty infiltration.…”
Section: Figures 1-4 Regression Line Of Multiple Linear Analysis For Predicting Blood Bhb In Cowsmentioning
confidence: 74%